Validation, Verification, and Calibration: Using Standardized Terminology When Describing Ecological Models - Frank J. Mazzotti; Joy J. Vinci (EDIS, 2007)
WEC-216, a 2-page fact sheet by Frank J. Mazzotti and Joy J. Vinci, discusses briefly the philosophical issues surrounding the use of ecological models and try to reduce confusion by providing definitions for these three key terms. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, April 2007.